Poverty Trends in Germany and Great Britain The Impact of Changes in Labour Markets, Families, and Social Policy - Brülle, Jan (Springer Fachmedien Wiesbaden : VS, 2018)
Jan Brülle shows how poverty risks in Germany between 1992 and 2012 increased concentrated on those with low educational levels, in lower occupational positions, and with precarious employment careers, as the country's welfare state failed to adapt to widening inequalities in households' market incomes. Contrasting the German experience with Great Britain, where social transfers to low-income families in concert with favourable labour market conditions helped to reduce poverty between 1992 and the global financial crisis, he presents the most comprehensive comparative study on poverty trends in these two countries to date. Moving beyond a cross-sectional perspective on poverty, the author analyses why it became not only more frequent in Germany, but also more persistent in individual life-courses, and why faster exits have driven the decline in poverty in Great Britain. Contents Concepts and Explanations of Poverty The Changing Structure of Poverty Risks Labour Market Risks, Households, Social Security The Dynamics of Relative Income Poverty Income Poverty and Material Deprivation Target Groups Lecturers and students of sociology, social policy, economics Practitioners working in social policy The Author Dr. Jan Brülle is a researcher at Goethe-University Frankfurt. His research focuses on the interrelations of labour markets, families and social policy and their impact on poverty and social inequality.